2010
DOI: 10.1007/s10725-010-9510-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of artemisinin content and biomass in Artemisia annua by exogenous GA3 treatment

Abstract: Artemisinin is a promising and potent antimalarial drug naturally produced by the plant Artemisia annua L. but in very low yield. Its artemisinin content is known to be greatly affected by both genotype and environmental factors. In this study, the production of artemisinin and leaf biomass in Artemisia annua L. was significantly increased by exogenous GA 3 treatment. The effect of GA 3 application on expression of proposed key enzymes involved in artemisinin yield was examined in both wild type (007) and FPS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 40 publications
2
39
0
1
Order By: Relevance
“…Exogenous GA treatment can increase artemisinin production in A. annua (Weathers et al, 2005;Zhang et al, 2005;Aftab et al, 2010;Banyai et al, 2011). However, the molecular mechanism of GA-modulated artemisinin production remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous GA treatment can increase artemisinin production in A. annua (Weathers et al, 2005;Zhang et al, 2005;Aftab et al, 2010;Banyai et al, 2011). However, the molecular mechanism of GA-modulated artemisinin production remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3). However, Zhang et al (2005) reported no difference in the transcription pattern of ADS gene by RNA gel blot analysis, while upregulation of FDS , ADS and CYP71AV1 in response to GA3 has been reported by Banyai et al (2010). At 72 h after treatment, all of the studied genes were down-regulated, ranging from 7.5-to 46.5-fold, which was accompanied with a consequent reduction in artemisinin to the same level as in control plants.…”
Section: Resultsmentioning
confidence: 87%
“…An application of exogenous GA3 on A. annua plants significantly increased the production of artemisinin, up-regulating three genes in its biosynthesis pathway and inducing the conversion of artemisinic acid to artemisinin (Zhang et al, 2005;Banyai et al, 2010). However, in recent research no induction of artemisinin biosynthesis by GA3 was reported (Maes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also suggested that there is a crosstalk between the ABA signaling pathway and the artemisinin biosynthetic pathway, and that CYP71AV1 (amorpha-4,11-diene C-12 oxidase gene), which was induced most significantly, may play a key regulatory role in the artemisinin biosynthetic pathway. Banyai et al (2011) observed enhancement of artemisinin content and leaf biomass in A. annua by exogenous GA 3 treatment. The increased artemisinin content was associated with an increased synthesis of key enzymes in the artemisinin biosynthesis pathway due to the GA 3 application.…”
Section: Effect Of Phytohormones and Amino Acidsmentioning
confidence: 75%